Use of Technology in Tax Administrations 3 : Implementing a Commercial-Off-The-Shelf (COTS) Tax System - Cotton, Margaret (Technical Notes and Manuals; Technical Notes and Manuals ;, 2017)
This technical note is the third of three addressing information technology (IT) themes and issues relevant to tax administrations. This note focuses on implementation of a commercial-off-the-shelf (COTS) system in a developing country tax administration. The first note covers the use of IT in tax administrations and how to develop an information technology strategic plan (ITSP). The second note addresses how to select a suitable information technology system for core tax administration functions. These technical notes are primarily tax administrations that have no technology to manage their core tax processes, or their technology is limited and outdated. These notes focus on core tax functions and do not address other business systems (e.g., payroll, finance, document, and asset management systems).